Strategi Pengembangan Ekonomi Kreatif Mahasiswa Ekonomi Syariah Institut Syekh Abdul Halim Hasan Binjai - Syahfitri, Nadia; Hendra, Hendra (LPPPIPublishing, 2026)
This study examines the strategy for developing the creative economy among students of the Sharia Economics Program at Institut Syekh Abdul Halim Hasan Binjai using a qualitative field research approach. Data were collected through in-depth interviews, observations, and documentation involving lecturers, program administrators, and student entrepreneurs. The findings indicate that the development strategy integrates an entrepreneurship-based curriculum, institutional mentoring, collaboration with local micro-enterprises, and the utilization of digital platforms for marketing and branding. Students primarily engage in halal culinary and digital creative businesses, applying Islamic ethical principles such as honesty, transparency, and social responsibility in their operations. Despite positive progress, challenges including limited capital, time management constraints, and financial literacy gaps persist. The novelty of this research lies in proposing a multidimensional strategic model that combines maqashid al-sharia principles with campus-based business incubation and digital transformation, positioning the creative economy as a value-driven empowerment instrument within Islamic higher education.